2013
DOI: 10.1186/1479-5876-11-259
|View full text |Cite
|
Sign up to set email alerts
|

A first-in-human, phase 1, dose-escalation study of dinaciclib, a novel cyclin-dependent kinase inhibitor, administered weekly in subjects with advanced malignancies

Abstract: BackgroundDinaciclib, a small-molecule, cyclin-dependent kinase inhibitor, inhibits cell cycle progression and proliferation in various tumor cell lines in vitro. We conducted an open-label, dose-escalation study to determine the safety, tolerability, and bioactivity of dinaciclib in adults with advanced malignancies.MethodsDinaciclib was administered starting at a dose of 0.33 mg/m2, as a 2-hour intravenous infusion once weekly for 3 weeks (on days 1, 8, and 15 of a 28-day cycle), to determine the maximum adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 43 publications
5
94
1
2
Order By: Relevance
“…Inhibiting CDK9 is known to cause minimal toxicity to normal cells (Lemke et al 2014, Li et al 2015. In vivo mouse xenograft models and phase I clinical trials have also shown that CDK9 inhibition results in minimal toxicity while maintaining effective antitumor activity (Abdullah et al 2011, Feldmann et al 2011, Nemunaitis et al 2013. Therefore, targeting CDK9 may offer safe and effective therapeutic strategy for patients afflicted with the advanced stages of PCa.…”
Section: :12mentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibiting CDK9 is known to cause minimal toxicity to normal cells (Lemke et al 2014, Li et al 2015. In vivo mouse xenograft models and phase I clinical trials have also shown that CDK9 inhibition results in minimal toxicity while maintaining effective antitumor activity (Abdullah et al 2011, Feldmann et al 2011, Nemunaitis et al 2013. Therefore, targeting CDK9 may offer safe and effective therapeutic strategy for patients afflicted with the advanced stages of PCa.…”
Section: :12mentioning
confidence: 99%
“…Structurally, this could be attributed to the large amount of shared features among the CDK family, particularly at the ATPbinding pocket, where current inhibitor discovery efforts are focused on. These structural similarities cause CDK9 Multiple clinical trials for hematologic and solid tumors (Parry et al 2010, Desai et al 2013, Flynn et al 2013, Nemunaitis et al 2013, Kumar et al 2015, Baker et al 2016 (Joshi et al 2007, Manohar et al 2011, Mishra et al 2013 www.clinicaltrials.gov…”
Section: Development Of Pharmacological Inhibitors Of Cdk9 For Pcamentioning
confidence: 99%
“…5,6 European population-based analyses have similarly revealed suboptimal outcomes in this population. [7][8][9][10] Emerging novel agents provide substantial antileukemic effect with manageable toxicity and may represent attractive therapeutic strategies for older patients with ALL, either as components of initial therapy or as treatment at relapse. [11][12][13][14][15] There remains a paucity of data reflecting clinical outcomes in older US adults with ALL, particularly outside clinical trials, which provides historical context for evaluating novel approaches.…”
Section: Org Frommentioning
confidence: 99%
“…6 Dinaciclib is a novel, potent, small-molecule CDK inhibitor that selectively inhibits CDK1, 2, 5, and 9 at 50% inhibitory concentration values in the 1-to 4-nM range. 7,8 In in vitro studies, dinaciclib induced apoptosis and/or cell growth arrest in various solid and hematopoietic tumor cell models. [9][10][11] Additionally, dinaciclib produces caspaseindependent downregulation of messenger RNA and protein expression of the antiapoptotic protein myeloid cell leukemia 1 (MCL1), which is essential for CLL cell survival.…”
mentioning
confidence: 99%
“…Dinaciclib (MK-7965, formerly SCH727965), a novel, selective CDK1-4/7/9 inhibitor with improved therapeutic index, was found to induce apoptosis in CLL cells (Johnson, et al 2012). It has already been tested in initial trials for solid tumours (Nemunaitis, et al 2013), myeloma (Kumar, et al 2015) 5 and refractory CLL (Flynn, et al 2015). Encouraging Phase I and II results provide a rationale for the use of dinaciclib alone or in combination with immunotherapies in CLL and lymphoma (Blachly, et al 2016).…”
Section: Introductionmentioning
confidence: 99%